Multiple dimensions of niche specialization explain changes in species’ range area, occupancy, and population size - Di Cecco, Grace J.; Hurlbert, Allen H. (Frontiers in Ecology and Evolution, 2022)
In response to environmental change, species may decrease or increase in population size across their range, expand or contract their range limits, or alter how sites are occupied within their existing range. Shifts in range limits and widespread changes in population size have been documented in birds especially in response to changes in climate. Range occupancy, or how patchily or continuously a species is distributed within their range, has been studied less in the context of anthropogenic changes but may be expected to decrease with range-wide population size if abundance-occupancy relationships are generally positive. Determining which properties of species are related to range expansion or contraction or increased range occupancy or decreased range occupancy is useful in developing an understanding of which species become “winners” or “losers” under global change. Species with broader climatic niches may be more likely to successfully expand to new sites as climate changes. Range occupancy can be related to habitat preferences of species, and habitat specialization may predict how species fill in sites within their range. To examine how species niche breadth may explain changes in species distributions, we modeled how changes in range-wide population size, range extent, and range occupancy from 1976 to 2016 were predicted by species’ climate, habitat, and diet niche breadth for 77 North American breeding bird species. We found that climate generalists were more likely to be increasing in range area, while species with declining population trends were likely to be contracting in range area and in occupancy within their range. Understanding how different dimensions of specialization relate to shifts in species distributions may improve predictions of which species are expected to benefit from or be vulnerable to anthropogenic change.